The Impact of Leadership and Human Resource Development on Organizational Performance: A Case Study of KFC Store - Fitriani, Maya; Anggraeni, Lola (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This study examines the significant effects of leadership and human resource (HR) development on organizational performance at KFC stores. The results indicate that effective leadership and strategic HR development initiatives are crucial for enhancing employee productivity, job satisfaction, and overall performance. Specifically, the average leadership score was 19.4, showing a moderate to strong correlation with organizational performance. Likewise, HR development practices scored an average of 18.75, which also positively impacted performance outcomes. By aligning leadership with HR development, organizations can create a supportive work environment that fosters improved productivity and job satisfaction. This research emphasizes the synergy between leadership and HR development as a key driver of organizational success. However, factors such as organizational culture and external influences should also be considered for a more comprehensive understanding. Future research should explore the combined effects of leadership and HR development in various organizational contexts.